A NEW METHOD POWER POINT TRACKING WEAR METHOD DC-DC CONVERTER BASED ON FUZZY LOGIC OF BAYU POWER PLANT - Zuraidah Tharo (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2019)
In increasing the electric power capacity of the Bayu Power Plant (PLTB) there are several ways among others by increasing the number of plants, but the weakness is that the costs are too expensive because they have to build a new generator. Another way is to improve the efficiency of the power output existing wind power plants. One way is to use technology Maximum Power Point Tracking (MPPT) which functions to increase power output electricity generator when there is a change in wind speed. In this paper, this technology in charge of regulating the output voltage of the generator through a DC-DC Converter type Cuk Converter, where the switching technique uses PWM (Pulse Width Modulation) with set the amount of the duty cycle. Change the value of the duty cycle depends on the size of the speed wind, so as to set the duty cycle value and speed up the PWM control switching response used a modern algorithm called Fuzzy Logic Controller (FLC). Research result shows that, with FLC-based MPPT technology can increase the percentage of efficiency PLTB output power from 45.5% to 87%.